(untitled) (Heritage, 2025)
The novel Zmajevi od papira (Paper Dragons) by Mira Otašević (2008), based on the biography of architect Selman Selmanagić, represents a unique blend of fictional and documentary elements in a hybrid genre form. Its aim is to portray the narrator’s life journey and the horrors of internal turmoil that reflect on the external world and events, indicating its transience during the Second World War and the immediate periods before and after. The motif of fire, which serves as a central metaphor, is analyzed through its relationship with other stylistic figures, stylistic and lexical invariants, intertextuality, and other significant motifs. These contribute to the notion of fire as a blatant political book burning, where books and degenerate art suffer incidentally, as well as the fervor of individuals. Therefore, it is appropriate to use the mentioned neologism exceptionally. However, the motif of flickering fire in the novel, depicted through the sparks produced by human kindness, raises the question of whether fire as the product inevitably leads to mere ashes or if there exists a ray of wonder. The aim of the paper is to present the Little Anthology of the Architecture of Hell, as the narrator calls his notebook, through an analytical-synthetic method in which the evil and wonder of the world coexist in the same syntagma.